Examples of Computing the Modulus of a Complex Number

Example 1: Modulus of -5 -2i is √((-5)2+(-2)2) = √29 = 5.39
Example 2: Modulus of -1 is √((-1)2+(0)2) = √1 = 1.0
Example 3: Modulus of 1 -1i is √((1)2+(-1)2) = √2 = 1.41
Example 4: Modulus of 1+3i is √((1)2+(3)2) = √10 = 3.16
Example 5: Modulus of -3+3i is √((-3)2+(3)2) = √18 = 4.24
Example 6: Modulus of 1 -4i is √((1)2+(-4)2) = √17 = 4.12
Example 7: Modulus of -4i is √((0)2+(-4)2) = √16 = 4.0
Example 8: Modulus of -4 -3i is √((-4)2+(-3)2) = √25 = 5.0
Example 9: Modulus of -3i is √((0)2+(-3)2) = √9 = 3.0
Example 10: Modulus of -3 -1i is √((-3)2+(-1)2) = √10 = 3.16
Example 11: Modulus of -4i is √((0)2+(-4)2) = √16 = 4.0
Example 12: Modulus of -2i is √((0)2+(-2)2) = √4 = 2.0
Example 13: Modulus of -4i is √((0)2+(-4)2) = √16 = 4.0
Example 14: Modulus of -3 -3i is √((-3)2+(-3)2) = √18 = 4.24
Example 15: Modulus of 1+4i is √((1)2+(4)2) = √17 = 4.12
Example 16: Modulus of -4 -1i is √((-4)2+(-1)2) = √17 = 4.12
Example 17: Modulus of 4 -5i is √((4)2+(-5)2) = √41 = 6.4
Example 18: Modulus of 1 -1i is √((1)2+(-1)2) = √2 = 1.41
Example 19: Modulus of -1i is √((0)2+(-1)2) = √1 = 1.0
Example 20: Modulus of 4 -2i is √((4)2+(-2)2) = √20 = 4.47
Example 21: Modulus of 2+1i is √((2)2+(1)2) = √5 = 2.24
Example 22: Modulus of 3 -1i is √((3)2+(-1)2) = √10 = 3.16
Example 23: Modulus of 4 is √((4)2+(0)2) = √16 = 4.0
Example 24: Modulus of 1 -4i is √((1)2+(-4)2) = √17 = 4.12
Example 25: Modulus of 4 is √((4)2+(0)2) = √16 = 4.0
Example 26: Modulus of 1+3i is √((1)2+(3)2) = √10 = 3.16
Example 27: Modulus of -4 -3i is √((-4)2+(-3)2) = √25 = 5.0
Example 28: Modulus of 3 is √((3)2+(0)2) = √9 = 3.0
Example 29: Modulus of -1 is √((-1)2+(0)2) = √1 = 1.0
Example 30: Modulus of -2 -3i is √((-2)2+(-3)2) = √13 = 3.61